**(i) - 8m – 2 = -10**

⇒ -8m = -10 + 2 ⇒ -8m = -8

⇒ m = -8/-8 ⇒ m = 1

**(ii) 4x + 2x = 3 + 5**

⇒ 6x = 8 ⇒ x = 8/6

⇒ x = 4/3 ⇒ x = 1.1/3

**(iii) 4x – x + 5 = 8**

⇒ 3x + 5 = 8 ⇒ 3x = 8 – 5

⇒ 3x = 3 ⇒ x = 3/3 = 1

**(iv) 6x + 2 = 2x + 10**

⇒ 6x – 2x = 10 – 2 ⇒ 4x = 8

⇒ x = 8/4 ⇒ x = 2

**(v) 18 – (2a – 12) = 8a**

⇒ 18 – 2a + 12 = 8a

⇒ -2a – 8a = -18 – 12

⇒ -10a = -30

⇒ a = -30/-10

⇒ a = 3

**(vi) 3x + 5 + 2x + 6 + x = 4x + 21**

⇒ 6x + 11 = 4x + 21

⇒ 6x – 4x = 21 – 11

⇒ 2x = 10

⇒ x = 10/2

⇒ x = 5

**(vii) 3.5x – 9 – 3 = x + 1**

⇒ 3.5x – x = 1 + 9 + 3

⇒ 2.5x = 13 ⇒ x = 13/2.5

⇒ x = (13 × 10)/25 ⇒ x = 26/5 or 5.1/5

**(viii) 8x + 6 + 2x – 4 = 4x + 8**

⇒ 10x + 2 = 4x + 8

⇒ 10x – 4x = 8 – 2

⇒ 6x = 6 ⇒ x = 6/6

⇒ x = 1

**(ix) – m + (3m – 6m) = - 8 – 14**

⇒ -m + 3m – 6m = -8 – 14

⇒ -7m + 3m = -22

⇒ -4m = -22

⇒ m = -22/-4 ⇒ m = 11/2

⇒ m = 5.1/2

**(x) 5x – 14 = x – (24 + 4x)**

⇒ 5x – 14 = x – 24 – 4x

⇒ 5x + 4x – x = -24 + 14

⇒ 9x – x = -10

⇒ 8x = -10 ⇒ x = -10/8

⇒ x = - (5/4) or -1.1/4